1997
DOI: 10.1901/jaba.1997.30-181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choosing Academic Assignments on a Student With Attention Deficit Hyperactivity Disorder

Abstract: The effects of choosing academic assignments on the undesirable behaviors manifested by a second-grade student with attention deficit hyperactivity disorder were analyzed. This study extended Dunlap et al.'s (1994) research on choice making as a form of antecedent control. A reversal design showed that undesirable behaviors decreased when the student was given a choice of academic assignments.DESCRIPTORS: antecedent control, behavior management, classroom managementClassrooms have been identified as being prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 2 publications
0
53
1
2
Order By: Relevance
“…However, this design could not be appropriately implemented in the four play sessions that were available. In contrast, the reversal, withdrawal, or ABAB design was one that could be feasibly conducted in a limited amount of time and which had been used in previous experimental research [43,44,56].…”
Section: Methodsmentioning
confidence: 99%
“…However, this design could not be appropriately implemented in the four play sessions that were available. In contrast, the reversal, withdrawal, or ABAB design was one that could be feasibly conducted in a limited amount of time and which had been used in previous experimental research [43,44,56].…”
Section: Methodsmentioning
confidence: 99%
“…The interventions that were included in this category (see Table 1) focused on the application of behavior modification techniques (Fabiano & Pelham, 2003;Northup et al, 1999;Van Lier, Muthen, Van der Sar, & Crijnen, 2004), cognitive-behavioral techniques (Ardoin & Martens, 2004;DuPaul & Hoff, 1998;Mathes & Bender, 1997), or environmental changes that involve modifications in the usual classroom dynamics (Powell & Nelson, 1997;Ridgway, Northup, Pellegrin, LaRue, & Hightsoe, 2003). Decrease disruptive behavior and increase "on-task" behavior.…”
Section: Simple Interventionsmentioning
confidence: 99%
“…Northup et al (1999) Addition of behavioral consequences may further enhance MPH effects. Powell & Nelson (1997) 1 Age: 7…”
Section: Simple Interventionsmentioning
confidence: 99%
“…Providing choices to individuals with disabilities has been encouraged within interventions as a means to develop autonomy as well as being an important part of the normalization process (Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997). A number of investigations have shown that allowing individuals to make choices between tasks or reinforcing consequences is an effective technique in both decreasing maladaptive behavior and increasing compliance to instructions (Powell & Nelson, 1997;Romaniuk et al, 2002).…”
Section: Choice Proceduresmentioning
confidence: 99%